COMPARATIVE STUDY OF MALE AND FEMALE PURCHASE INTENTIONS TOWARD COLOR OF CITY CAR IN MANADO - Somba, Windah Estrilia (Universitas Sam Ratulangi, 2014)
Many people want products with attractive color. The product’s color may play a significant role in the consumer’s purchase intentions for certain products. It strongly influences the elegant, price, design of products like City Car. The objective of this research is to find out if there is any significant difference between male and female purchase intention toward color of city car in Manado. The type of this research is comparative study. This research use quantitative method and Independent sample T-test to analyze the data. This research is conducted in Manado. Population of this research is people in Manado who wants to buy and already have a City Car. The sample of this research is 100 respondents, consist of 50 respondents of male, and 50 respondents of female. The result of this study is, there is no significant different between male and female purchase intention toward color of city car. People in Manado does not really care about color of car because color is not important factor when they plan to buy a city car. A lot of people choose city car because it has a lower price, attractive design, economical gasoline, and flexible. Suggestion for all manager of city car, do not care too much with color when produce the city car. Keywords: purchase intention, color